EKSPRESI GORESAN GARIS DAN WARANA DALAM KARYA SENI LUKIS - Aldi Yunaldi (Besaung : Jurnal Seni Desain dan Budaya, 2016)
In the essence of painting was not out of line and color, it was very important in a painting. Line was a basic element in art that mean more than just a scratch, Role lines were very important in the process embodiment form, because the line determines the quality of expression of an artist who appeared in strokes or in granting certain accentuation on the object creation. When the line was structured, such as arranged through rhythm, symmetry, balance would form certain patterns so that the line was able to speak as a medium of expression. Likewise with color, an outline of the meaning of the colors that we could actually described its. With a record if the colors were in a state of stand alone or be dominant compared with other colors. Scientifically, understanding of color was an electromagnetic wave that led to our eyes were translated by the brain as a color. In other words, the colors were also something to do with human emotions. And it could cause psychological influence. Keywords : Expression, Emotion, line, colour.